Partial pulpotomy on caries-free teeth using enamel matrix derivative or calcium hydroxide: a randomized controlled trial - Kiatwateeratana, T.; Kintarak, S.; Piwat, S.; Chankanka, O.; Kamaolmatyakul, S.; Thearmontree, A. (International endodontic journal, 2009)
Aim  To compare the effect of enamel matrix derivative (EMD) and calcium hydroxide [Ca(OH)2] on exposed human pulp. Methodology  Fifteen pairs of human contralateral premolars were intentionally and partially pulpotomized. The exposed pulps were randomly capped with either EMDgel (Emdogain®) or a mix of Ca(OH)2 and sterile water. The subjects recorded pain or discomfort during the first 10 days and were also interviewed and examined by a blinded examiner at 1 day, 2 weeks, 3 and 6 months post‐operation. Periapical radiographs were taken prior to the operation, and 3 and 6 months post‐operation. After 6 months, the teeth were extracted and processed for histological evaluation. The data were described and analysed using McNemar test and Kaplan–Meier survival analysis. Results  The EMDgel‐treated teeth had significantly less tooth hypersensitivity than the Ca(OH)2‐treated teeth during the first 2 weeks (P = 0.031) but were not significantly different after 2 weeks (P = 0.125). No detectable periapical radiographic changes were observed in any teeth and radiographic evidence of dentine bridge formation from both groups were not significantly different during the follow‐up periods (P > 0.05). Histological evaluation demonstrated that the Ca(OH)2‐treated teeth had less inflammation and more dentine bridge formation than those in the EMDgel‐treated teeth. Conclusions  After 6 months, healthy pulps capped with Ca(OH)2 had more favourable results than counterparts capped with EMDgel. However, similar clinical and radiographic results were seen in both groups.